Guselkumab for the treatment of psoriasis: a 60-week real-life multicenter retrospective experience. (2nd December 2022) - Bardazzi, Federico; Viviani, Filippo; Merli, Yuri; Di Lernia, Vito; Peccerillo, Francesca; Conti, Andrea; Lasagni, Claudia; Tabanelli, Michela; D'Adamio, Simone; Di Nuzzo, Sergio; Cortellazzi, Chiara; Filippi, Federica
ABSTRACT: Background: Real-world data for guselkumab, the first interleukin-23 inhibitor approved to treat moderate-to-severe psoriasis, are scarce. This study represents the first 60-week, real-life, multicenter, retrospective experience to investigate the effectiveness, safety, tolerability, and drug retention of guselkumab in psoriatic patients. Research design and methods: Clinical information was collected at baseline and at weeks 12, 24, 36, 48, and 60. Results: The mean baseline Psoriasis Activity Severity Index (PASI) reduced from 14.2 to 3.1 at week 12 and decreased to around 0 at weeks 36, 48, and 60. PASI 75, PASI 90, and PASI 100 were 100%, 96.8%, and 83.9% at week 60, respectively. Multiple logistic regression analysis showed that neither body mass index >30, smoking, ≥3 comorbidities, difficult-to-treat areas, nor a failure to ≥2 prior biologic treatments significantly influenced PASI reduction (p > 0.05). Conclusions: Our findings confirm guselkumab as an appropriate therapeutic option in routine clinical practice, especially when dealing with complex patients with comorbidities or previous failure to biologic treatments.